The Ecological Aspects of Local Pottery in Guilan, Iran - Ziaee, Majid; Nadalian, Ahmad; Marasy, Mohsen (Journal of History Culture and Art Research, 2017)
The modern world is facing pervasive environmental problems and pollution crisis, while in the previous eras, meeting one's need through environment would inflict less harm on one's surroundings. In traditional artifacts, compatibility with the natural environment does exist and in many aspects has been suited with the climate and environmental features of every locality. The main purpose of the study is to identify and introduce the environmental features of pottery of Guilan, Iran. This is achieved by investigating the interaction between the local potters and their environment. The primary data are collected through library resources, field observation and visiting active potteries in Guilan. In this regard, the main research questions of the present study are as follows: What are the features of Guilan local pottery? What features are compatible with environmental standards? To conduct the study, a descriptive-analytical method is employed. The findings show that pottery in Guilan is not a threat to the environment in terms of local knowledge in using raw material, finding resources of renewable energy, community-based manpower, optimum exploitation of time and energy, potteryware designing with various functions, and re-using a product for further purposes. Nonetheless, there exist some issues which are not environmentally friendly like failure to modernize the potteryware to be of use for current needs, high rate of waste over the production process, and using toxic materials in glazing. Therefore, raising environmental awareness of locals, cultural diffusion, informing the users of the benefits of using pottery, and making improvements to the cycle of design, producing, and marketing all play substantial role in preserving local pottery.